Knowledge of India’ in NEP 2020 Key to Restore Pride in School Children - Ojha, Seema Shukla; Seema Shukla Ojha (JOURNAL OF INDIAN EDUCATION, 2021)
The National Education Policy 2020 (NEP 2020) envisions an education system, which can instill among the learners a deep-rooted pride in being Indian, one who understands and appreciates India’s rich cultural heritage, the contribution of Indian civilisation to the world civilisation in different spheres of life such as science, art, architecture, heritage, philosophy, etc. Considering that the ancient knowledge in various fields have a great potential and relevance for the future also, NEP recommends ‘Knowledge of India’ to be taught as one of the core subjects, to be learned by all the students. At the same time, it proposes that these rich Indian legacies to the world heritage must not only be nurtured and preserved for posterity but also researched, enhanced, and put to new uses through our education system. The paper elaborates on the importance of this knowledge area in the school curriculum and suggests possible ways, methods and strategies to help our students have a proper perspective of India’s heritage and a legitimate pride in belonging to this civilisation based on objective knowledge.